Cellulose Degrading Ability of Bacterial Strains Isolated from Gut of Termites in Vinhlong Province - Vietnam - Thanh Phong Ngo (AIDIC Servizi S.r.l., 2021)
Cellulose are the most abundant renewable biomass. The bioconversion of cellulose plays an important role for sustainable development and application in alcohol production, compost production and waste treatment. Termites were known as the most successful wood-degrading species on the earth, can degrade in large quantities of cellulosic biomass by activities of enzymes secreted by the termites and/or their gut. A total of 70 bacterial isolates were isolated from the gut of termites obtained from thirteen termite nests in TraOn district, VinhLong province, Mekong Delta, Vietnam. Of the 70 bacterial isolates, 60 (86%) are able to degrade CMC (Carboxyl Methyl Cellulose) after culturing in media containing CMC agar and halo formation after staining with Congo red. Among of them, 5 isolates having high CMC degradation efficiency are chosen to evaluate the potential ability to liberate glucose from cellulose of straw for 5, 10, 15 and 20 days respectively at room temperatures. The results showed that all of the 5 isolates have the cellulose degradation ability and produce the highest glucose contents after 15 days. Out of the 5 isolates, 2 produced glucose in large quantities are 2T1 isolate (0.73 g/L) and 5T6 isolate (0.79 g/L) in hydrolysis solutions. The 2T1, 5T6 strains were 98.99%, 99.01% of identity Paenibacillus humicus strain T20C, Psychrobacter faecalis strain AP3Ka respectively by 16S rRNA genes sequencing and could be potential sources of enzymes for cellulose hydrolysis from cellulosic biomass in future.